2022
DOI: 10.3329/jom.v23i1.57942
|View full text |Cite
|
Sign up to set email alerts
|

IPSID- a Neglected Cause of Chronic Diarrhea

Abstract: immunoproliferative small intestinal disease is considered as a rare condition and has endemicity inMediterranean countries and often associated with campylobacter jejuni infection. This conditionvaries in severity from benign to frankly malignant. Prolonged remission can be obtained with longterm antibiotic therapy but chemotherapy is required for those who have aggressive disease. Bangladeshidata on IPSID is sparse. Here our patient 21 years old male presented with chronic diarrhoea, occasionalvomiting, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…If left untreated can lead to higher grade of b-cell lymphomas, GI bleeding, malnutrition, morbidity and mortality. [1,2] Median diagnostic time is 10 months from the onset of earlier symptoms. Most of the people are successfully diagnosed for the disease when they develop the above-mentioned symptoms and report mild symptoms like diarrhea from the past several years.…”
Section: Symptoms and Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…If left untreated can lead to higher grade of b-cell lymphomas, GI bleeding, malnutrition, morbidity and mortality. [1,2] Median diagnostic time is 10 months from the onset of earlier symptoms. Most of the people are successfully diagnosed for the disease when they develop the above-mentioned symptoms and report mild symptoms like diarrhea from the past several years.…”
Section: Symptoms and Diagnosismentioning
confidence: 99%
“…Here, we were able to analyze PVC i.e., N-acetylmuramoyl-L-alanine amidase for development of vaccine against IPSID (Immuno proliferative small intestine disease) which was selected as a PVC by vaxign program [4], with the help of Vaxi-DL and VaxELAN [5,6] in terms of adhesion, secretory nature, trans-membrane helices, cleavage sites, MHC-I binding, CTL epitope prediction, essential genes, molecular weight, non-bacterial pathogen, non-homology with human genome, virulence factors, allergenicity, cellular localization and probability of being a PVC. IPSID is a disease emerging from the low socio-economic background areas such as in mediterranean regions and later spread as sporadic cases increased in European and American countries [1]. C. jejuni is the major and common pathogens found in studies amongst other groups of microbes found in the patients [2].…”
Section: Symptoms and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations